IMPLEMENTATION OF ZONE PARKING POLICY IN MAYJEND SUNGKONO, SURABAYA CITY - Ressa Fitriana; Diana Hertati (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2021)
Transportation is very necessary for its role in the development of a country, not only smoothing the flow of goods and mobility well but through long-term development. Parking problems are not new anymore. Based on the Surabaya City Regional Regulation Number 3 of 2018 concerning the Implementation of Parking in the City of Surabaya, parking is defined as a vehicle that stops or does not move for a while and is abandoned by the driver. The parking problem occurs in almost all cities in Indonesia, including the city of Surabaya. The implementation of Zone Parking itself is carried out by collecting retribution in accordance with the applicable Zone Parking levy rates. The purpose of this research is to find out the problems regarding the implementation of the parking zone determination policy in the Mayjend Sungkono area, Surabaya City. The method used in this research is descriptive qualitative with interviews and direct observation to the relevant informants. From this study it can be seen that the implementation of the zone parking policy has been going well, this can be seen through the smooth start of the function routine and the absence of complicated problems faced. During the current pandemic, the problem that occurs in parking is the reduction in parking retribution income due to the PPKM period where there is less public activity outside the public. The Surabaya City Transportation Service seeks to minimize problems that occur in zone parking for the successful implementation of zone parking policies in Surabaya City, so that road users and other motorists are not disturbed due to traffic jams caused by chaotic parking.